Phytonematode peptide effectors exploit a host post‐translational trafficking mechanism to the ER using a novel translocation signal. Issue 1 (22nd July 2020) - Wang, Jianying; Dhroso, Andi; Liu, Xunliang; Baum, Thomas J.; Hussey, Richard S.; Davis, Eric L.; Wang, Xiaohong; Korkin, Dmitry; Mitchum, Melissa G.
Summary: Cyst nematodes induce a multicellular feeding site within roots called a syncytium. It remains unknown how root cells are primed for incorporation into the developing syncytium. Furthermore, it is unclear how CLAVATA3/EMBRYO SURROUNDING REGION (CLE) peptide effectors secreted into the cytoplasm of the initial feeding cell could have an effect on plant cells so distant from where the nematode is feeding as the syncytium expands. Here we describe a novel translocation signal within nematode CLE effectors that is recognized by plant cell secretory machinery to redirect these peptides from the cytoplasm to the apoplast of plant cells. We show that the translocation signal is functionally conserved across CLE effectors identified in nematode species spanning three genera and multiple plant species, operative across plant cell types, and can traffic other unrelated small peptides from the cytoplasm to the apoplast of host cells via a previously unknown post‐translational mechanism of endoplasmic reticulum (ER) translocation. Our results uncover a mechanism of effector trafficking that is unprecedented in any plant pathogen to date, andthey illustrate how phytonematodes can deliver effector proteins into host cells and then hijack plant cellular processes for their export back out of the cell to function as external signaling molecules to distant cells. Abstract : See also the Commentary on this article by Frei dit Frey & Favery 229 : 11–13 .